Penerapan Model Problem Based Learning terhadap Pemahaman Materi “Norma dalam Kehidupanku” pada Siswa SDN 3 Sumberejo - Siti Nur Maulidiyah; Muhamad Irham Darojat; Susilo Tri Widodo; Yunika Ucik Purwita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the application of Pancasila Education learning on thesubject of Norms in My Life at SD Negeri 3 Sumberejo and to identify efforts toimprove student understanding through the Problem Based Learning (PBL) model.The research method used is descriptive qualitative with observation, tests, andinterviews techniques. The results of the study indicate that learning withoutconcrete media is not yet optimal, while the application of PBL assisted by concretemedia in the form of dioramas of norms is able to increase student activity andunderstanding. In conclusion, Pancasila Education learning will be more effective ifit uses the PBL model supported by concrete and contextual media.